Ochromobactrum intermedium: an emerging opportunistic pathogen—case of recurrent bacteraemia associated with infective endocarditis in a haemodialysis patient. (January 2017) - Bharucha, T.; Sharma, D.; Sharma, H.; Kandil, H.; Collier, S.
Abstract: We describe the first clinical case report of infective endocarditis related to Ochrobactrum intermedium infection. The case involved a 23-year-old man receiving dialysis via an internal jugular long-term haemodialysis catheter. He improved with a prolonged course of meropenem and minocycline. Ochrobactrum spp. are recognized as rare emerging opportunistic pathogens.